Perceived Deception in Upward Organizational Communication: An Examination of Information Manipulation Theory - Mittal, R.; Randhawa, V. (Indian Journal of Extension Education, 2021)
The thrust of the study was to examine Information Manipulation Theory (IMT) during upward communication in an Indian organizational cultural context. To test IMT theory, stimulus material in the form of a hypothetical interactional situation between superior and subordinate was prepared and presented before the faculty of the academic organization for testing the efficacy of violated messages along the four dimensions of IMT i.e. Quantity, Quality, Relevance and Clarity. The results revealed that all the violations were perceived different than the baseline (honest) message along the respective dimensions. Further, results suggest that all violations were considered deceptive, though with varying degrees. Amongst all, quality violation was perceived as most deceptive while quantity violation was perceived as least deceptive form of information manipulation. Interestingly, the results were in conformity to preceding studies conducted to test the claims of the theory in western cultures and partially similar to those conducted in non western cultures. The study directs towards the need for multi situational and multidirectional research at international level for generalization of the theory across cultures.
Keywords: Information manipulation theory; Organizational communication; Organizational deception; Upward communication